Archaeological Record as Archaeological Heritage - Zafra de la Torre, Narciso (Complutum, 2017)
The archaeological heritage is defined by its methodology and not by its values, consequently archaeological discipline and its professionals are involved in their definition. In adidition, a part of the methodology – archaeological recordinvestigates the findings and its inventory, then determines the archaeological public domain. By archaeological public domain the legislature awarded better protection to the archaeological heritage, as long as there was not threat of plundering and therefore must be retired from market. This menace demonstrates that the archaeological heritage is an undesiderable heritage, and therefore can not be the result of a social convention. From the above it is inferred that the entire archaeological record is, and must remain, historical heritage.
Keywords: Archaeological Heritage; Archaeological Record; Archaeological Public Domain; Methodology